IMPROVING GERMAN NARRATIVE TEXT WRITING SKILLS WITH THE HELP OF SERIALIZED IMAGES WITH THE THINK TALK WRITE LEARNING MODEL - Misnah Mannahali; Alamsyah; Femmy Angreany (LLDIKTI Wilayah X, 2024)
This study aims to describe the effect of the application of the Think, Talk, Write learning model assisted by serialized images on improving the German narrative writing skills of SMA Negeri 1 Bone students. The study population was all students of SMA Negeri 1 Bone who studied German. While the sample used is a total sample, which is taken from the entire population of 30 people, the research data were obtained by using initial observation and tests, namely the pretest and posttest. The collected data were analyzed using the T test by first finding the average value of the two tests. From the results of the data analysis obtained, the value of the t-count was 9.923 > than the t-table was 2.048 at a significance level of 0.05%. In addition, the average score obtained by students on the pretest was 68.24%, which was below the value of learning completeness. While the average value obtained by students in the post-test is 84.11, this shows an increase of 15.87%. These results indicate that the Think, Talk, Write learning model assisted by serialized images can significantly improve the German narrative writing skills of SMA Negeri 1 Bone students.